2023
DOI: 10.3390/cancers15194808
|View full text |Cite
|
Sign up to set email alerts
|

SLAM Modification as an Immune-Modulatory Therapeutic Approach in Cancer

Alireza Tojjari,
Francis J. Giles,
Maysa Vilbert
et al.

Abstract: In the field of oncology, the Signaling Lymphocyte Activation Molecule (SLAM) family is emerging as pivotal in modulating immune responses within tumor environments. The SLAM family comprises nine receptors, mainly found on immune cell surfaces. These receptors play complex roles in the interaction between cancer and the host immune system. Research suggests SLAM’s role in both enhancing and dampening tumor-immune responses, influencing the progression and treatment outcomes of various cancers. As immunotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…CD150 is a self-ligand considered to have a notable role in adhesion and in signaling in the immune synapse between T cells and antigen-presenting cells ( 30 ). Moreover, CD150 may be involved in cancer malignancy and autoimmune disorders, including inflammatory bowel syndrome, rheumatoid arthritis, multiple sclerosis, hepatitis, systemic lupus erythematosus and XLP ( 3 - 5 , 31 ). The results of the present study demonstrated that CD150 was gradually expressed on the B cell surface during EBV infection and was fully expressed on the surface after 4 weeks of EBV exposure.…”
Section: Discussionmentioning
confidence: 99%
“…CD150 is a self-ligand considered to have a notable role in adhesion and in signaling in the immune synapse between T cells and antigen-presenting cells ( 30 ). Moreover, CD150 may be involved in cancer malignancy and autoimmune disorders, including inflammatory bowel syndrome, rheumatoid arthritis, multiple sclerosis, hepatitis, systemic lupus erythematosus and XLP ( 3 - 5 , 31 ). The results of the present study demonstrated that CD150 was gradually expressed on the B cell surface during EBV infection and was fully expressed on the surface after 4 weeks of EBV exposure.…”
Section: Discussionmentioning
confidence: 99%